Pemberdayaan Ekonomi melalui Pengolahan Hasil Pertanian Desa Dayakan Kecamatan Badegan Kabupaten Ponorogo - Teguh Ansori (Islamic Management and Empowerment Journal, 2024)
poverty in Indonesia is the largest contributor to the number of farmers. This is because farmers have not received special attention from the government. Even though Indonesia is a fertile country, many farmers are still at the poverty line. For example, farmers in Sekar Putih hamlet, Dayakan Village, Badengan District, Ponorogo Regency. Farmers will be more productive during the rainy season, and will become consumptive farmers during the dry season. This is because in the dry season, farmers do not cultivate their agricultural land, and only rely on plants planted in the rainy season. The method used in this service activity is ABCD (Asset Based Community Development) in which community empowerment uses an asset approach. Local assets around the community that have not been used for empowerment are used as empowerment capital. The results of the mapping of assets in the Sekar Putih hamlet, Dayakan Village, show that farmers have assets in the form of agricultural products, namely cassava. Cassava is made into a cassava layered sponge cake to have a high selling value. So that the result of processing assets in the form of cassava is able to improve the economy of farmers